2019
DOI: 10.1002/asi.24238
|View full text |Cite
|
Sign up to set email alerts
|

Examining users' partial query modification patterns in voice search

Abstract: This article investigates how to improve the effectiveness of voice search systems. Earlier research found that participants employed voice search much less frequently than keyboard search. The main reasons that participants disliked voice search are system mistakes and the inability to modify queries. In keyboard search, query reformulation is facilitated by partial query modification, which is not supported by most of the current voice search systems. Consequently, users need to speak the complete query in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
(70 reference statements)
1
11
0
Order By: Relevance
“…There are some inherent challenges in developing conversational systems, including but not limited to the absence of cognition and the dynamic nature of the search process. Findings from prior research (Sa & Yuan, 2020; Turunen et al, 2012; Luger & Sellen, 2016) have highlighted that conversation systems are task‐based and incapable of performing complex or exploratory search tasks.…”
Section: Discussionmentioning
confidence: 99%
“…There are some inherent challenges in developing conversational systems, including but not limited to the absence of cognition and the dynamic nature of the search process. Findings from prior research (Sa & Yuan, 2020; Turunen et al, 2012; Luger & Sellen, 2016) have highlighted that conversation systems are task‐based and incapable of performing complex or exploratory search tasks.…”
Section: Discussionmentioning
confidence: 99%
“…To complete the query reformulation, in the baseline system, the participants had to speak the new query completely “when was television invented?” In the experimental system, the participants needed to modify the previous query by saying “change movie to television .” To make the system less complicated and to reduce the learning load of the users, only three common voice commands (Table 1) from (Sa & Yuan, 2020b) were implemented.…”
Section: Methodsmentioning
confidence: 99%
“…Among the few studies about reformulation operations during voice search, Allauzen et al (2012) built a model which could support voice query refinements of insert, delete, and substitute, and trained a system based on typed query logs. In our previous work (Sa & Yuan, 2020b), we conducted a Wizard of Oz user‐centered experiment to investigate how users would partially modify the previous query by speaking to the system. We found that when given the opportunity of editing the previous query by voice, the participants conducted more partial QMs than complete queries.…”
Section: Previous Workmentioning
confidence: 99%
“…Virtual assistance like Amazon Alexa, Cortana, Viv, Cortana and Siri use voice search on search engine. Google has noted that more than twenty percent of mobile device searches are done using voice search (Sa and Yuan, 2020).…”
Section: Use Of Ict In E-commercementioning
confidence: 99%